The effects of antioxidant supplementation on pain, oxidative stress markers, and clinical pregnancy rate in women with endometriosis: a systematic review and meta-analysis of randomized controlled trials - Zhong, Yuchan; Qiao, Xinyu; Huang, Xin; Li, Yujing; Wang, Ruiying; Liang, Jiagui; Liu, Tingting; Bo, Wenjie; Lai, Huiqiao; Huang, Wei (Frontiers in Medicine, 2025)
Endometriosis is a chronic inflammatory disease characterized by pelvic pain and infertility, with oxidative stress playing a key role in its pathogenesis. Although antioxidant supplementation has been proposed as a potential adjunctive therapy in endometriosis, current evidence regarding its efficacy in symptom relief and fertility improvement remains inconclusive. This systematic review and meta-analysis included 21 randomized controlled trials involving 1,626 participants and evaluated more than 10 types of antioxidant supplementation, including vitamins, pentoxifylline, melatonin, astaxanthin, fish oil, and silymarin. The results showed that antioxidant supplementation significantly alleviated pelvic pain (continuous outcomes: SMD = −2.68; p < 0.00001; binary outcomes: RR = 9.31; p < 0.0001), dysmenorrhea (SMD = −1.77; p = 0.01; RR = 2.39; p = 0.03), and dyspareunia (SMD = −2.33; p = 0.01; RR = 5.40; p = 0.003), and significantly decreased peripheral blood malondialdehyde (MDA) levels (SMD = −7.58; p = 0.001). However, no significant effects were observed on overall pain (SMD = −1.14; p = 0.51) or clinical pregnancy rate (RR = 1.12; p = 0.52). Subgroup analyses further indicated that treatment efficacy varied by antioxidant type, disease stage, and duration of intervention. These findings suggest that antioxidant supplementation may offer therapeutic benefits in alleviating specific pain symptoms and reducing oxidative stress in women with endometriosis. Further large-scale and high-quality randomized controlled trials are needed to validate these results and establish optimal antioxidant strategies for long-term management of endometriosis.Systematic review registrationPROSPERO CRD420251071723, https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD420251071723.